(untitled) (Revista Contexto & Educação, 2025)
This article presents a political-epistemological in the field of qualitative research, effort in order to highlight the cyberfascist cartography that corrupts democracy, in the framework of the of pure war focused on counter-information unleashed in contemporaneity. In this context the Enlightenment Pedagogy is proposed as a path to bear the authoritarian offensive. This is education as a practice of freedom in the face of the viral pandemic of fake news, which imposes the false sometimes as a cosmetic, sometimes as a poison of the real to pave the way for the predatory advance of ultraliberalism.